A label-free homogeneous electrochemical cytosensor for the ultrasensitive detection of cancer cells based on multiaptamer-functionalized DNA tetrahedral nanostructures. Issue 27 (5th March 2020) - Yang, Limin; Yin, Xuehan; Gai, Panpan; Li, Feng
Abstract : A label-free homogeneous electrochemical cytosensor was developed for ultrasensitive detection of cancer cells based on multiaptamer-functionalized DNA tetrahedral nanostructures. Abstract : We developed a label-free homogeneous electrochemical cytosensor for ultrasensitive detection of cancer cells based on multiaptamer-functionalized DNA tetrahedral nanostructures, which avoided expensive labeling and sophisticated immobilization procedures, providing opportunities for precisely detecting cancer cells in clinical applications.